Diagnosis and Screening Strategies for Detection of Familial Hypercholesterolaemia in Children and Adolescents in Italy: A Survey from the LIPIGEN Paediatric Group - Cristina Pederiva; Federica Galimberti; Manuela Casula; Giuseppe Banderali; Guglielmo Beccuti; Vanessa Bianconi; Giacomo Biasucci; Marta Biolo; Marco Bucci; Paola Sabrina Buonuomo; Paolo Calabrò; Stefano Carugo; et al. (Children)
Background: Awareness, diagnosis, and treatment of familial hypercholesterolemia (FH) starting from childhood are a cornerstone of cardiovascular disease prevention. The LIPIGEN Paediatric Group, a network of specialised centres for the diagnosis and management of familial genetic dyslipidemia, is an active part of this mission. Materials and Methods: This is the second exploratory survey organised within the LIPIGEN (LIpid transPort disorders Italian GEnetic Network) paediatric centres. A digital questionnaire consisting of 16 questions was proposed to the principal investigators of 35 LIPIGEN centres in September 2023. We analysed the main FH screening strategies implemented in Italy, which are the referral characteristics to the lipid clinics and clinical and biochemical criteria considered to diagnose FH in paediatric patients. Results: Centres frequently reported conducting cascade screening (88.6%) and reverse screening (57.1%), whereas 28.6% of respondents indicated using selective screening and only 5.7% reported employing child–parent screening. We documented a detailed biochemical characterisation of paediatric patients (62.9% of respondents usually perform full lipoprotein profile and 80% determine lipoprotein(a) for each patient) and a high percentage of genetic analysis (82.9%). We have also highlighted a quite low awareness of FH as a genetic condition involving paediatric patients among primary care paediatricians and general practitioners. Conclusions: The results of our survey show that specialised lipid centres usually have good diagnostic competence when dealing with paediatric patients with hypercholesterolemia. However, FH awareness and the importance of early diagnosis and treatment initiation in childhood still need to be further improved.